Lindung Nilai Kontrak Forward Untuk Mengurangi Risiko Eksposur Transaksi - Agung Pramayuda; Siti Hawa Salsabila; Nisrina Nur Duriyah; Siti Jasmin Aulia Azzahra; Indarta Priyana (Economics Professional in Action (E-Profit), 2024)
Fluctuations in foreign exchange rates are one of the risks that must be faced by companies, especially multinational companies. Many companies use hedging methods when carrying out international trade transactions. The aim of this research is to analyze hedging activities using forward contracts carried out by PT. Unilever Indonesia Tbk, to reduce the risk of transaction exposure. The research method used is descriptive qualitative with secondary data sources. The research results show that one forward contract transaction in the first quarter of 2023 was carried out by PT. Unilever against the USD currency does not fulfill the hedging objective because the forward rate in the agreed contract is higher than the spot rate at the maturity of the contract.